DODA IDI POEM AND TRANSMISSION OF ETHNO-NATIONALISM SPIRIT IN THE ACEH COMMUNITY - Muhaini, Muhaini; Nasir, Mohd. (UIN Sumatera Utara, 2020)
Abstract: This paper discusses the transmission of ethnonationalism spirit in an Acehnese society based on the doda idi poem case study. The scholarship about Aceh contemporary shows the high commitment of ethnonationalism as the social identity of its people. But, the studies that discuss these themes have not given adequate attention to the use of poetry as a social mechanism in reproducing and transmitting the spirit of ethnonationalism. Based on qualitative data collected through in-depth interviews, observation, and documentation studies, this paper proposes the argument that the transmission of the spirit of ethnonationalism in Acehnese society across generations begins with social mechanisms that take place within the scope of the family. Dodas poems chanted by almost every mother in Aceh when they put their children to sleep as infants have a significant role in the process of forming collective identity and ethnonationalism in the future. Correspondingly, this article concludes that ethnonationalism awareness transmitted through poetry operates in two consciousnesses that are interconnected with each other, namely; discursive consciousness and practical consciousness. Keywords: doda idi poetry, Aceh’s collective identity, ethnonationalism